2011
DOI: 10.1523/jneurosci.1519-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Activation of Frontal, Parietal, and Sensory Regions Underlying Anticipatory Visual Spatial Attention

Abstract: Although it is well established that multiple frontal, parietal and occipital regions in humans are involved in anticipatory deployment of visual spatial attention, less is known about the electrophysiological signals in each region across multiple sub-second periods of attentional deployment. We used MEG measures of cortical stimulus-locked, signal-averaged (ERF) activity during a task in which a symbolic cue directed covert attention to the relevant location on each trial. Direction-specific attention effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
51
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 74 publications
15
51
1
Order By: Relevance
“…The lingual gyrus has a role in the processing of emotional stimuli, such as faces (Fusar-Poli et al, 2009), unpleasant pictures (Aldhafeeri et al, 2012) and words presented in negative contexts (Maratos et al, 2001). SMA constitutes a link between emotion and motor control (Mazzola et al, 2013), whereas superior and middle frontal gyrus are involved in both cognitive and affective tasks: visuo-spatial attention (Simpson et al, 2011), orienting/executive attention (Fan et al, 2005) and emotion regulation (Blair et al, 2007). In an fMRI study conducted on young unaffected offspring of BD patients, Ladouceur et al (2013) reported alterations in the functioning of fronto-limbic systems implicated in voluntary emotion regulation, during an emotional working memory task.…”
Section: Discussionmentioning
confidence: 99%
“…The lingual gyrus has a role in the processing of emotional stimuli, such as faces (Fusar-Poli et al, 2009), unpleasant pictures (Aldhafeeri et al, 2012) and words presented in negative contexts (Maratos et al, 2001). SMA constitutes a link between emotion and motor control (Mazzola et al, 2013), whereas superior and middle frontal gyrus are involved in both cognitive and affective tasks: visuo-spatial attention (Simpson et al, 2011), orienting/executive attention (Fan et al, 2005) and emotion regulation (Blair et al, 2007). In an fMRI study conducted on young unaffected offspring of BD patients, Ladouceur et al (2013) reported alterations in the functioning of fronto-limbic systems implicated in voluntary emotion regulation, during an emotional working memory task.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported to mediate direction-specified and selectionrelated attention. 51,52 Wang et al 53 examined the sensation threshold during rectal distention in IBS patients and found that distracting their attention by talking and reading markedly increased the threshold of sensation in these patients. 53 This documented that selective attention of gastrointestinal symptoms is the cognitive-behavioral characteristic of IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent MEG study by Simpson and others (2011) examined the time course of direction-specific and direction-unspecific responses in several regions of interest after the onset of a centrally presented spatial cue that oriented attention to the left or right hemifield (see Fig. 4).…”
Section: Top-down Biases Emerging From the Dorsal Systemmentioning
confidence: 99%